Meld Score Predicts Lvad Operative Transfusion Requirements, Morbidity, and Mortality - Matthews, Jennifer C. (2010)
BACKGROUND: The Model for End-Stage Liver Disease (MELD) predicts events in cirrhotic subjects undergoing major surgery and may offer similar prognostication in LVAD candidates with comparable degrees of multisystem dysfunction. METHODS AND RESULTS: Preoperative MELD scores were calculated for subjects enrolled into the University of Michigan Health System (UMHS) mechanical circulatory support database. Univariate and multiple regression analyses were performed to investigate the ability of patient characteristics, laboratory data (including MELD scores), and hemodynamic measurements to predict total perioperative blood product exposure (TBPE) and operative mortality. The ability of preoperative MELD scores to predict operative mortality was evaluated in subjects enrolled into the Interagency Registry of Mechanically-Assisted Circulatory Support (INTERMACS), and results were compared to the UMHS cohort. The mean±standard deviation MELD scores for the UMHS (n=211) and INTERMACS (n=324) cohorts were 13.7±6.1 and 15.2±5.8, respectively, with 29 (14%) and 19 (6%) perioperative deaths. In the UMHS cohort, median [25(th),75(th)] TBPE was 74 [44,120] units. Each 5-unit MELD increase was associated with 15 [7.6,23] units of TBPE. Each 10-unit increase in TBPE increased the odds of operative death; OR [95%CI] =1.05 [1.01,1.10]. Odds ratios, measuring the ability of MELD scores to predict perioperative mortality, were 1.5 [1.1,2.0] and 1.5 [1.1,2.1] per 5 MELD-units for the UMHS and INTERMACS cohorts, respectively. When MELD scores were dichotomized as ≥17 and <17, risk-adjusted Cox proportional hazard ratios for 6-month mortality were 2.5 [1.2,5.3] and 2.5 [1.1,5.4] for the UMHS and INTERMACS cohorts, respectively. CONCLUSIONS: The MELD score identified LVAD candidates at high risk for perioperative bleeding and mortality.